Motivation and Engagement Strategies in Language Learning - Tinaz, Nuri (The Lingua Spectrum, 2024)
Motivation and engagement are pivotal for successful second language acquisition (SLA). This article examines the theoretical foundations, practical strategies, and challenges associated with motivating language learners. Drawing on research from key sources and empirical studies, the discussion provides insights into best practices for fostering engagement and motivation in language learning contexts.